PERANAN ADVOKAT DALAM MELAKUKAN PENDAMPINGAN KEPADA KORBAN PENGANIAYAAN DAN PENGEROYOKAN (Studi di Kepolisian Daerah Sumatera Utara) - Sagala, Hasiholan; Manullang, Herlina (Judge : Jurnal Hukum, 2025)
Advocates have a strategic role in the criminal justice system, especially in the North Sumatra Regional Police (Polda), as the main actor in ensuring the protection of legal for victims of criminal acts of persecution and beatings. As independent law enforcers, advocates not only function to provide legal consultation and assistance, but also play a role in overseeing the course of the investigation process to remain in line with the principle of the Due Process of Law and the principle of justice. In addition to litigation function, Advocates also carry out educational roles through empowerment of victims in order to understand their rights and are able to actively participate in the legal process. However, the implementation of the strategic role still faces various obstacles. Based on interviews with Advocates Yosua T. R. Panjaitan, there are several obstacles faced, including geographical obstacles in reaching remote areas, limited mentoring costs, and ethical challenges in the form of practicing bribes and potentially disturbing external pressures Law enforcement objectivity. Based on these conditions, this study emphasizes the importance of sustainable reform through improving professional integrity, utilization of digital technology in legal aid services, as well as strengthening the mechanism of internal and external supervisory to advocate performance. This effort is expected to realize a fairer, transparent, transparent and oriented criminal justice system on the protection of the victim.